2020
DOI: 10.1080/14461242.2020.1785321
|View full text |Cite
|
Sign up to set email alerts
|

Risk perception, coronavirus and precariousness. A reflection on fieldwork under quarantine

Abstract: On 19 March 2020, I last met with a group of women from a neighbourhood of Monterrey, Mexico where I have spent the past year conducting ethnographic research. They had scheduled a meeting to decide whether to continue our weekly talks on health-related topics. 'Is this coronavirus real?' was the question guiding the meeting. Women shared their thoughts on their feelings on the threat that predominates in biomedical discourse. An air of resignation pervaded their speech. Nearly all of them suffer from chronic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 7 publications
(5 reference statements)
0
12
0
Order By: Relevance
“…Risk-related understandings and practices are highly interdependent with factors such as numbers of COVID cases in participants’ place of residence, the tenor of news reporting in their locale and their observations of how other people they see in their locale behave. Other influences are people’s own state of health as well as their age, occupation, religious faith, educational background, political views or trust in experts or government [13] , [14] , [15] , [16] , [17] , [18] . Indepth qualitative research conducted in countries as diverse as Côte d’Ivoire [19] , Nigeria [20] , England [21] , Switzerland [22] , Sweden [23] and China [24] have demonstrated the intersections of such sociocultural factors with ideas about COVID vaccination acceptance, hesitancy or rejection.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Risk-related understandings and practices are highly interdependent with factors such as numbers of COVID cases in participants’ place of residence, the tenor of news reporting in their locale and their observations of how other people they see in their locale behave. Other influences are people’s own state of health as well as their age, occupation, religious faith, educational background, political views or trust in experts or government [13] , [14] , [15] , [16] , [17] , [18] . Indepth qualitative research conducted in countries as diverse as Côte d’Ivoire [19] , Nigeria [20] , England [21] , Switzerland [22] , Sweden [23] and China [24] have demonstrated the intersections of such sociocultural factors with ideas about COVID vaccination acceptance, hesitancy or rejection.…”
Section: Introductionmentioning
confidence: 99%
“…This scholarship has shown that understandings of human immunity have evolved from the ‘attack’ and ‘defence’ model of the early twentieth century [30] towards the concept of the porous, precarious and dynamic immune system [31] . People now often think of immune systems as being unique to the individual, based on their health history and lifestyle [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations